Relasi Kehidupan Suami-Istri dalam Perspektif Al-Qur’an - Saidah, Zahrotus (El 'Ailaah, 2025)
This article discusses the relationship between husband and wife life in the perspective of the Qur'an with a focus on Surah An-Nisa verses 12-23. These verses provide in-depth guidance on the division of rights and duties between husband and wife, as well as the principles of justice, compassion, and mutual respect in domestic life. This research aims to explore the values contained in these verses and their relevance in building a harmonious husband-wife relationship in the modern era. With a qualitative approach, this study uses the thematic interpretation method to explore the content of Qur'anic verses comprehensively. The results of the study show that the husband-wife relationship regulated in Surah An-Nisa verses 12-23 prioritizes the principle of complementarity and balance of rights and obligations, which is relevant to be applied in today's household life.